Invasive Electrical Neuromodulation for the Treatment of Painful Diabetic Neuropathy: Systematic Review and Meta‐Analysis. Issue 1 (26th June 2020) - Raghu, Ashley L. B.; Parker, Tariq; Aziz, Tipu Z.; Green, Alexander L.; Hadjipavlou, George; Rea, Rustam; FitzGerald, James J.
Abstract: Objectives: Neuromodulation is a treatment option for people suffering from painful diabetic neuropathy (PDN) unresponsive to conventional pharmacotherapy. We systematically examined the pain outcomes of patients with PDN receiving any type of invasive neuromodulation for treatment of neuropathic pain. Materials and Methods: MEDLINE and Embase were searched through 10 January 2020, without language restriction. All study types were included. Two reviewers independently screened publications and extracted data. Quantitative meta‐analysis was performed with pain scores converted to a standard 100‐point scale. Randomized controlled trial (RCT) scores were pooled using the inverse variance method and expressed as mean differences. Results: RCTs of tonic spinal cord stimulation (t‐SCS) showed greater pain improvement than best medical therapy at six months (intention‐to‐treat: 38/100, 95% CI: 29–47). By per‐protocol analysis, case series of t‐SCS and dorsal root ganglion stimulation (DRGS) showed improvement by 56 (95% CI: 39–73) and 55 (22–87), respectively, at 12 months. For t‐SCS, the rate of failing a therapeutic stimulation trial was 16%, the risk of infection was 4%, and the rate of lead problems requiring surgery to resolve was 4% per year of follow‐up. High‐frequency SCS and burst SCS both showed efficacy, with few patients studied. Conclusion: Efficacious, lasting and safe surgical pain management options are available to diabetic patients suffering from PDN. Tonic‐SCS is the established standard of treatment; however, other SCS paradigms and DRGS are emerging as promising treatments offering comparable pain benefits, but with few cases published to date. Randomized controlled trials are ongoing to assess their relative merits.